Review of Geodiversity and Geoheritage related sessions at the European Geosciences Union General Assemblies (GeoPatterns, 2024)
Sessions related to geoheritage have been held under different convenorships and titles since 2012 at the European Geosciences Union General Assembly in Vienna. 2020 was a special year, since the session was held online. The author participated with a contribution in 2019 and without one in 2020, and it was an occasion to compare a physical session with oral and poster presentations and a splinter meeting to a digital session.